(untitled) (Research, Society and Development, 2021)
Predictive mathematical models have been proposed in alkali-silica reaction (ASR). Predicting concrete degradation and its effects on mechanical properties is of interest given the long time until degradation becomes critical for intervention and recovery, and difficult structural access for predictive and corrective monitoring and treatment. The present paper presents a general overview of the evolution of the aforementioned predictive mathematical models, interrelating them to the maturation of the phenomenological state of the art associated with ASR. For this purpose, a systematic literature review was used, followed by bibliometric analysis and meta-analysis. In this study, 104 articles from 1974 to 2020 were selected, of which 31 articles were reviewed on the topic of mathematical modeling of ASR. The results of the method indicated the importance of the methodological approach of literature review to provide a comprehensive and chronological view of the evolution of ASR consolidated in the literature. It was found that the mathematical models have evolved considering the phenomenological approach of ASR.